Overcoming Barriers to Breastfeeding: Suggested Breastfeeding Promotion Programs for Communities in Eastern Nova Scotia - Hogan, S. Eileen (Can J Public Health, 2001)
The 1994 rate of initiation of breastfeeding in eastern Nova Scotia was 41%. The purpose of this study is to assess both perceived barriers to breastfeeding as well as the need for programs to promote breastfeeding in this region. Seventy randomly selected subjects (67 F, 3 M) responded to a questionnaire about regional breastfeeding practices. Results showed that perceived barriers to breastfeeding included lack of knowledge about breastfeeding management (35.8%) and lack of support (29.9%). Barriers to exclusive breastfeeding for 6 months included going back to work (76.5%) and lack of support (39.2%). To promote exclusive breastfeeding for 6 months, participants recommended access to: prenatal classes (98.5%), nurse follow-up following hospital discharge (95.3%), and availability of lactation consultants (88.3%). When proposed promotion programs were implemented, breastfeeding initiation increased to 60.5% and duration rates increased to 4 months (90.2%). Regional barriers to breastfeeding can be partly alleviated through educational and support programs.